Penerapan Pemantapan Mutu Internal terhadap Kualitas Sediaan Pewarnaan Ziehl Nielsen untuk Deteksi Mycobacterium TB - Achmadi Achmadi; Maya Marhaeni Mardiah; Syafrima Wahyu (Jurnal Ilmiah Kesehatan (JIKA), 2021)
The Ziehl Neelsen method is used as a microscopic examination of Acid Fast Bacteria (BTA) and is a commonly used examination in diagnosing tuberculosis caused by Mycobacterium tuberculosis (M.TB) infection. The quality of the microscopic examination of AFB determines the quality of the tuberculosis control program, so to obtain the quality of the results of microscopic examination of AFB, it is necessary to be supported by quality reagents. The purpose of this study was to determine the relationship of internal quality stabilization to the quality of the preparation and the quality of the reagents. This research is quantitative research using a cross-sectional design. The sample in this study was 45 samples of AFB preparations with a total sampling technique. Data were analyzed by using the Spearman rank correlation test. The results of observations of internal quality stabilization, preparation quality, and reagent quality proportionally have been carried out well. The results of this study indicate that there is a significant relationship between internal quality assurance and dosage quality (0.000 <0.05) and internal quality improvement with reagent quality (0.000 <0.05).